Responses of a tidal freshwater marsh plant community to chronic and pulsed saline intrusion. (24th April 2022) - Li, Fan; Angelini, Christine; Byers, James E.; Craft, Christopher; Pennings, Steven C.
Abstract: Climate change causes both chronic and pulsed environmental changes to ecosystems. In estuaries, tidal freshwater marshes experience both extended and episodic periods of elevated salinities due to sea level rise, reduced river discharge during drought and storm surge, but most research has focused on extended (press) perturbations. Over a 4‐year period, we added diluted seawater to replicated plots in a tidal freshwater marsh in Georgia, USA to raise porewater salinities from freshwater to oligohaline. We assessed the ecosystem effects of press (continuous) and pulse (2 months per year) changes in salinity by measuring the responses of dominant angiosperms, benthic microalgae and dominant macro‐invertebrates (fiddler crabs). We transplanted angiosperms typical of oligohaline and mesohaline conditions into plots as bioindicators (phytometers) to assess potential for vegetation changes over longer time periods. In the press treatment, the cover of all common plant species decreased. Ludwigia repens almost disappeared within the first month; Polygonum hydropiperoides nearly disappeared within the first growing season; Pontederia cordata and Zizaniopsis miliacea declined over the 4 years but did not completely disappear. The decline in the four most dominant plant species decreased total above‐ground plant biomass, leading to an increase in light penetration and increased densities of benthic diatoms and cyanobacteria. The density of fiddler crab burrows was not significantly affected by the treatments, but was positively related to above‐ground plant biomass across all replicates. Transplant experiments indicated that plants typical of higher salinity conditions (e.g. Schoenoplectus sp.) performed well under conditions prevalent in the press plots. In the pulse treatment, only L. repens declined, and there was no effect on community‐level above‐ground biomass or other community variables. S ynthesis . Our results indicate that tidal freshwater marsh plant and animal communities are vulnerable to extended periods of salinization but resilient to short saline pulses. Although saline pulses did not impair most ecosystem functions, the decline in a single species ( L. repens ) in the pulse treatment was associated with reduced marsh accretion and no elevation gain—factors which must be positive for wetland survival in an era of rising seas. Thus, periodic salinization may threaten the long‐term persistence of freshwater wetlands even before dramatic changes in community structure occurs. Abstract : Climate change causes both chronic and pulsed environmental changes to ecosystems. Tidal freshwater marsh communities were vulnerable to extended periods of salinization but mostly resilient to short saline pulses. However, short saline pulses were associated with reduced marsh accretion, indicating that change in function can occur before dramatic changes in community structure. 摘要: 全球气候变化造成生态系统持续和暂时的环境改变。由于海平面上升、干旱导致的河流流量下降及风暴潮的影响，河口地区的潮汐淡水沼泽湿地经历着持续和暂时的盐度升高胁迫，但是大部分研究只关注于长期(持续)的干扰。 在位于美国佐治亚州的一块潮汐淡水沼泽湿地实验样方内，我们连续四年添加稀释海水，将土壤间隙水盐度由淡水水平提高至寡盐水平。我们通过测定优势被子植物、底栖微藻和优势大型底栖动物(招潮蟹)的响应来评估长期的(持续的)和短期的(每年两个月)盐度升高对生态系统的影响。我们将典型生长于寡盐和中盐盐度水平的被子植物移栽到实验样方中作为生物指示，来评估长期植被变化的潜在趋势。 在持续盐水入侵实验处理中，所有植物物种的盖度都有所下降。匍匐丁香蓼( Ludwigia repens )在第一个月内就几乎完全消失；梭鱼草( Pontederia cordata )和 Zizaniopsis miliacea 盖度在四年内均降低，但并没有完全消失。四大优势植物种盖度的降低使总地上生物量减少，这提高了光照透过量，并且增加了底栖硅藻和蓝细菌的密度。招潮蟹洞穴密度并没有受实验处理的显著影响，而是与植物地上生物量呈正相关关系。移栽实验结果表明，适应较高盐度水平的典型植物(如水葱属植物[ Schoenoplectus sp.])在持续盐水入侵实验样方中可正常生长。 在暂时盐水入侵实验处理中，只有匍匐丁香蓼( L. repens )盖度降低，而实验处理对植物群落地上生物量和其它群落水平变量无显著影响。 总结 . 本研究结果表明，潮汐淡水沼泽湿地动植物群落易受长期盐渍化的影响，但对短期盐水入侵干扰具有一定的弹性恢复力。尽管短期盐水入侵没有损害大部分生态系统功能，但其中一个植物物种( L. repens )盖度的降低与沼泽沉积物堆积及高程增益的减少密切相关，而这两个过程均是湿地在海平面上升的时代得以保存所必需的。因此，间歇的盐渍化可能在导致群落结构大规模改变发生之前就已威胁到了淡水湿地长期的持续稳定性。 Resumen: El cambio climático causa cambios ambientales crónicos y de pulso a los ecosistemas. En los estuarios, las marismas reciben períodos intermitentes y prolongados de salinidades elevadas causados por el aumento del nivel del mar, la descarga reducida de los ríos durante las sequias, y las marejadas ciclónicas, pero la mayoría de las investigaciones se han enfocado en las perturbaciones prolongadas (experimentos de presión). Durante un período de 4 años, agregamos agua de mar diluída sobre cuadrantes replicados en una marisma en Georgia, EEUU; para aumentar la salinidad del agua intersticial, desde agua dulce a oligohalina. Evaluamos los efectos de presión en el cambio de la salinidad cronica y de pulso (2 meses por año) en el ecosistema, midiendo las respuestas de las angiospermas dominantes, microalgas bentónicas y macroinvertebrados dominantes (cangrejos violinistas). Transplantamos angiospermas típicas de condiciones oligohalinas y mesohalinas en los cuadrantes como bioindicadores (fitómetros), para evaluar el cambio potencial en la vegetación durante largos períodos de tiempo. En el tratamiento de presión, la cobertura de todas las especies de plantas comunes disminuyó. Ludwigia repens casi desapareció dentro del primer mes; Polygonum hydropiperoides estuvo cerca de desaparecer dentro de la primera temporada de crecimiento; Pontederia cordata y Zizaniopsis miliaceai disminuyeron dentro de los 4 años, pero no desaparecieron completamente. La disminución de las cuatro especies de plantas más dominantes disminuyó la biomasa total de las plantas por encima del suelo, dando lugar a un incremento en la penetración de la luz y de las densidades de diatomeas bentónicas y cianobacterias. La densidad de las madrigueras del cangrejo violinista no fue significativamente afectada por los tratamientos, pero fue relacionada positivamente a la biomasa de las plantas por encima del suelo en todas las réplicas. Experimentos de transplante indicaron que las plantas típicas de las condiciones de más alta salinidad (e.g., Schoenoplectus sp.) se desempeñaron bien en los cuadrantes de presión bajo las condiciones persistentes. En el tratamiento del pulso, sólo L. repens disminuyó, y no hubo efecto sobre la biomasa por encima del suelo a nivel comunitario u otras variables comunitarias. Síntesis . Nuestros resultados indican que las comunidades de plantas y animales de las marismas son vulnerables a períodos prolongados de salinización, pero resilientes a los pulsos salinos cortos. Aunque los pulsos salinos no perjudicaron a la mayoría de las funciones ecosistémicas, la disminución de una sóla especie ( L. repens ) en el tratamiento de pulso, fue asociada con la reducción de la acumulación de la marisma y la falta del incremento en la elevación, los cuales deben ser positivos para la sobrevivencia de las marismas en una era de aumento del nivel del mar. Por lo tanto, la salinización periódica puede amenazar la persistencia a largo plazo de las marismas, incluso antes de que ocurran cambios drásticos en la estructura de la comunidad.